Perilaku bullying pada siswa sekolah dasar di Yogyakarta dan dampaknya - Apriani, An-Nisa; Putri, Mufida Awalia; Setiawan, Eko; Suyuti, Imam; Actaviana, Dira Ayu; Nafsi, Tazkiyatun (Universitas Sarjanawiyata Tamansiswa, 2026)
This study examines the factors, causes, impacts, and forms of bullying behavior in elementary schools. The method used to obtain an in-depth description of the phenomenon of bullying from the perspective of educators is qualitative descriptive. Data were obtained through questionnaires administered to teachers in Yogyakarta, describing their experiences and observations of bullying cases in the classroom and school environment. The results of the study found that the most dominant type of bullying was verbal bullying, in the form of teasing, name-calling, and belittling the appearance of friends. Physical and social bullying were also found, although to a lesser extent, while cyberbullying was relatively rare in elementary schools. The factors that influenced the emergence of bullying included difficulty controlling emotions, personal experiences, peer influence, differences of opinion, and unsupportive parenting patterns. The impacts felt by victims include decreased self-confidence, anxiety, sadness, and decreased motivation to learn, which in turn affects academic achievement. Meanwhile, bullies tend to feel a false sense of superiority or dominance but have the potential to lose empathy and have difficulty forming social relationships. These findings confirm that bullying in elementary schools is a serious problem that requires the joint attention of teachers, schools, parents, and the community.